The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1080/02619768.2012.682648
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the teacher/researcher divide: Master’s-level work in initial teacher education

Abstract: There is much current debate about the purpose and usefulness of educational research and the perceived communication gap between teaching professionals and academic researchers. UK government intervention into initial teacher education has in recent decades contributed to this divide by favouring school-based training. The most common route into teaching in England remains, however, the Postgraduate Certificate in Education, provided by higher education institutions and therefore required to comply with the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 16 publications
1
17
0
3
Order By: Relevance
“…The proliferation of teacher research, by and about teacher researchers, supports his claim yet also depicts how the field has grown more complicated 461 (Cochran-Smith & Lytle, 1999;Leeman & Wardekker, 2013). For example, teacher-led research has been found to provide opportunities for meaningful professional development (Vrijnsen-de Cortea, den Brok, Kamp, & Bergen, 2013), critical thinking (Hagevik, Aydeniz, & Rowell, 2012), discovery learning (Gray, 2013), collaborative collegial learning (Christie & Menter, 2009), university-school partnerships (Arhar et al, 2013;Thornley et al, 2004), and educational policy development (Rust & Meyers, 2006). Cochran-Smith and Lytle (1999) suggest that because teacher research "is such a generative concept, it can be shaped and reshaped to further virtually any educational agenda" (p. 17).…”
Section: Teachers As Researchers: Benefits Challenges and Time An mentioning
confidence: 84%
“…The proliferation of teacher research, by and about teacher researchers, supports his claim yet also depicts how the field has grown more complicated 461 (Cochran-Smith & Lytle, 1999;Leeman & Wardekker, 2013). For example, teacher-led research has been found to provide opportunities for meaningful professional development (Vrijnsen-de Cortea, den Brok, Kamp, & Bergen, 2013), critical thinking (Hagevik, Aydeniz, & Rowell, 2012), discovery learning (Gray, 2013), collaborative collegial learning (Christie & Menter, 2009), university-school partnerships (Arhar et al, 2013;Thornley et al, 2004), and educational policy development (Rust & Meyers, 2006). Cochran-Smith and Lytle (1999) suggest that because teacher research "is such a generative concept, it can be shaped and reshaped to further virtually any educational agenda" (p. 17).…”
Section: Teachers As Researchers: Benefits Challenges and Time An mentioning
confidence: 84%
“…ej., Gitlin et al, 1999;Gray, 2013;MacDonald et al, 2001). Esta discrepancia se disipa cuando se contrasta la imagen que los estudiantes de Magisterio tienen sobre la formación que reciben en investigación o cuando se analiza la vinculación entre la investigación y la práctica, ya que en estos tópicos vemos importantes puntos de encuentro.…”
Section: Discussionunclassified
“…ej., Demircioglu, 2008;Gitlin et al, 1999;Gray, 2013;Joram, 2007;Jyrhämä et al, 2008;MacDonald, Badger & Whites, 2001;Pendry & Husbands, 2000;van der Linden et al, 2012van der Linden et al, , 2015 han destacado tres grandes temas: la imagen de la investigación como un conocimiento alejado de la realidad, la percepción crítica de los programas de formación sobre estas temáticas y la necesidad de que la investigación proporcione recursos prácticos vinculados con la experiencia.…”
Section: Marco Teóricounclassified
“…Considering the affordances of the use small-scale projects, various studies have been conducted in order to incorporate teachers in research in different countries. In these studies, it is reported that conducting small-scale research projects provides opportunities to teachers to develop new insights about the research process (Gray, 2013;Trent, 2010), about their selected topic (Goodnough, 2010;MegowanRomanowicz, 2010), and about their own inquiry process as a practitioner (Freese, 2006;Reis-Jorge, 2007). According to Parkinson (2009), prospective teachers shift their perceptions about the role and needs of students when they are engaged in collaborative action research during teacher education.…”
Section: Incorporating Prospective Teachers Into Small-scale Researchmentioning
confidence: 99%